Cluster-induced desorption/ionization mass spectrometry of highlighter ink: unambiguous identification of dyes and degradation processes based on fragmentation-free desorption. Issue 2 (21st December 2021) - Bomhardt, Karolin; Schneider, Pascal; Rohnke, Marcus; Gebhardt, Christoph R.; Dürr, Michael
Abstract : The soft nature of cluster-induced desorption/ionization allows for unambiguous identification of highlighter inks and the discrimination of different degradation processes by means of mass spectrometry. Abstract : Highlighter inks were analyzed by means of soft Desorption/Ionization induced by Neutral SO2 clusters (DINeC) in combination with mass spectrometry (MS). The dye molecules of the different inks were directly desorbed from dots of ink drawn on arbitrary substrates. Fragmentation free spectra were observed and the dyes used in the dye mixtures of the different highlighter inks were unambiguously identified. The soft nature of cluster-induced desorption was used to investigate the decomposition of the dye molecules induced by either heat or UV-light. The two processes lead to different decomposition products which are clearly distinguished in the DINeC spectra. The two different degradation processes can thus be discriminated using DINeC-MS.